Comparison of accelerometer-measured sedentary behavior, and light- and moderate-to-vigorous-intensity physical activity in white- and blue-collar workers in a Japanese manufacturing plant - Fukushima, Noritoshi (J Occup Health, 2018)
OBJECTIVE: The times spent in sedentary behavior (SB) and moderate-to-vigorous physical activity (MVPA) are independently associated with health outcomes; however, objective data on physical activity levels including SB among different occupations is limited. We compared accelerometer-measured times spent in SB, light-intensity physical activity (LPA), and MVPA, and the patterns associated with prolonged bouts of SB between white- and blue-collar workers. METHODS: The study population consisted of 102 full-time plant workers (54 white-collar and 48 blue-collar) who wore a triaxial accelerometer during waking hours for 5 working days. Accelerometer-measured activity levels were categorized as SB (≤1.5 metabolic equivalents (METs)), LPA (1.6-2.9 METs), and MVPA (≥3.0 METs). A sedentary bout was defined as consecutive minutes during which the accelerometer registered less than ≤1.5 METs. Accelerometer variables were compared between white- and blue-collar workers through analysis of covariance. RESULTS: During working hours, white-collar workers spent significantly more time in SB and less time in LPA than blue-collar workers (SB: 6.4 h vs. 4.8 h, 73% vs. 55% of total work time; LPA: 1.9 h vs. 3.5 h, 22% vs. 40% of total work time, p<.001), whereas the MVPA time was similar between the groups. White-collar workers spent significantly more SB time in prolonged sedentary bouts (≥30 min) compared to blue-collar workers. During leisure time, the SB, LPA, and MVPA times were similar between the groups. CONCLUSIONS: White-collar workers have significantly longer SB times than blue-collar workers during work hours, and do not compensate for their excess SB during work by reducing SB during leisure time.